Effects of Kapok Seed Extract(Ceiba pentandra Gaertn) as Contraceptive Agent to the Quality of the Spermatozoa in Domestic Cat (Felis domestica) - Sitti Mughniati; Dwi Kesuma Sari; Dedy Rendrawan; Lellah Rahim (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2018)
Contraception is a way to prevent the fusion of mature egg cell and sperm during the intercourse, so the fertilization will not occur. Some contraceptive methods in small animals have been evolved. This research aimed to determine the effects of kapok seed (Ceiba pentandra Gaertn) extract as contraception agent to the quality of spermatozoain domestic cats. The animals were divided into four group with each group consisted of six male cats. Group I, II, III was designated as the treatment groups and IV as the control group. The cats were given the emulsion of kapok seeds extract orally with concentration of 0,1%  b/v, 0,71 mg/kg BB, 0,36 mg/kg BB and 0,21 mg/kg BB doses. This study used Randomized Complete Random Design (RAL) design from sperm quality data and used ANOVA statistic test. The result showed that the concentration of sperm decreased in the treatment groups compared with the control group. Statistically, the sperm concentration decreased significantly (P < 0,05) between the control group and treatment groups. The average motility in low and medium doses was above 40% while it was below than 40% in the high doses group. Based on the results, the granting of kapok seed extract inhibited the viability of spermatozoa of cats with significant results (P < 0,05). Sperm abnormalities in this study was obtained from the control group with percentage average of 1 % , while it was significantly increased in the treatment groups marked by abnormalities in the shape of the head and tail of the spermatozoa. These results suggested that kapok seed extract can be used as one of the contraceptive agents in domestic cat (Felis domestica) because it can decrease the sperm quality significantly.